ANALISIS PERTUMBUHAN MUDHARABAH BANK MEGA SYARIAH - dewi, ratna kusuma; Rais, Harisna (Journal Of Islamic Ekonomic and Business, 2023)
Abstract This article explains the evolution of Mudharabah in Bank Mega Syariah. Bank Mega Syariah organizes general banking with a profit-sharing system based on Islamic Sharia. and has been operating as a sharia commercial bank since October 16, 2008. Bank Mega Syariah is licensed as a foreign exchange bank. With this status, the bank can conduct foreign transactions and conduct international business. Through this article, the author would like to explain the growth of Mudharabah financing at Bank Mega Syariah. Although it is one of the Islamic banks in Indonesia. However, in 2018-2019 Bank Mega Syariah had a peculiarity where the increase in Mudharabah was not successful. This research uses quantitative methods and literature review methods with descriptive research types. Based on the report, we note that Bank Mega Syariah applies the principle of profit sharing, although there are often deviations in its application. Keywords: Mudharabah, assets, liability, equity, musyarakah